‫إسهامات ‬‫القيادة‬ ‫الاستراتيجية‬ ‫في‬ ‫تدريب‬ ‫الموارد‬ ‫البشرية‬‬ دراسة حالة اتصالات الجزائر سوق اهراس - ‫ماضي ‬‫موسى‬; ‫عبد‬‫الديم‬ ‫جميلة‬ (My University, 2019)
This study sought to highlight the role of strategic leadership and its most important practice: strategic direction, strengthening organizational culture, strengthening ethical practices, maintaining core competencies, and strengthening effective regulatory oversight, through the impact on human resource training and its ability to develop and change the performance of individuals. In order to achieve this objective, a field study was conducted in the Communication Department of Algiers in Souk Ahras. A questionnaire was designed for this purpose. It was distributed to a sample of 30 workers. The spss program was based on the data unloading and analysis. Test Assumptions and access to results. Our study shows that strategic leadership affects the training of human resources at the Algerian Communications Directorate - Souq Ahras